Mathematical Modeling and Computer Control of a Two-Phase Permanent-Magnet Stepping Motor - Wong, Richard C. S. (My University, 1973)
The analysis of stepping motors using linear models has been simplified through identifications of the constants. Though the existing nonlinear models assuming a smooth air-gap machine may, in some cases, yield a fairly close prediction of the characteristics of a stepping motor, the models do not represent the actual motors which are essentially salient-pole motors. A new salient-pole nonlinear model is introduced. The analysis of permanent-magnet stepping motors using the nonlinear models has been simplified by assuming constant current sources. Dynamic behaviors of a permanent -magnet stepping motor are shown by phase-plane plots and step by step transient response plots.
Computer control of stepping motors in both open-loop and closed-loop is discussed. The open-loop control has been demonstrated to be successful and a closed-loop control system using light-sensors as feedback has been designed.
Keywords: mathematical modeling, computer control, two-phase, permanent-magnet, stepping motor, loop